ATTITUDE - KEY ELEMENT OF COMPETENCE AND ESSENTIAL OBJECTIVE OF THE INSTRUCTIONAL-EDUCATIONAL PROCESS - Mihaela Aurelia ȘTEFAN (Universitaria Publishing House, Craiova, 2021)
Competence training is not limited to the assimilation of knowledge and strategies or to the formation of skills and abilities, but also to the formation of attitudes. In school we must promote values and attitudes such as: interest in reading and the pleasure of reading; autonomous, reflective and critical thinking in relation to the various assimilated information; self-confidence in one's own abilities; tolerance towards the opinions of others etc. In order to face the challenges of the contemporary world, people must adapt quickly and efficiently, to find solutions and timely strategies, in order to achieve the desired results and especially to find the resources necessary to go through changes several times during their life. In a complex situation, the mobilization of various cognitive resources is not a spontaneous and original invention, but goes through a series of spiritual operations that update the plans and sometimes apply methods. "Mental management", "neurolinguistic programming" and various methods of cognitive education help the subject to become aware of his thinking mechanisms. However, there is no universal "know-how" that applies regardless of cognitive resources or that can be identified with the subject's intelligence. The present study aims to present the importance of training and developping attitude in the Romanian school system. The current context confirms the need to assert a positive attitude, of openness to the new, combined with self-confidence, as absolutely essential directions to meet the demands of accelerated change and reconstruction. Formation and development of an appropriate attitude is an aspect often neglected in school, although in crisis situations, attitude is a key factor in overcoming and solving problems.